Is Iron Deficiency Anaemia, a risk Factor For Wheeze Associated Respiratory Tract Infection in Children? - Agrawal, A; Gupta, R; Sodhi, KD; Raghav, V (Journal of Nepal Paediatric Society, 2015)
Introduction: Wheezing is the common in children with cumulative prevalence of almost 50% by the age of 6 yrs. Iron deficiency anaemia is an independent risk factor for lower respiratory tract infections (LRTI), however may also play an important role in wheeze associated respiratory tract infection. The present study aimed at finding a correlation between iron deficiency anaemia and wheeze associated respiratory tract infection. Materials and Methods: This case control study was conducted at a multidisciplinary tertiary care hospital from Jul 2012 to Jun 2013 among children six months to five years and having ≥2 episodes of wheeze associated respiratory tract infections. The clinical presentation and laboratory profile were recorded on a predesigned performa. Iron deficiency anaemia was diagnosed by haemoglobin <11.0 gm%, serum ferritin<12ng/ml and RDW>15%. The statistical analysis was done using SPSS, Version 15.0. Results: A total of 100 children were enrolled in the study, of which 50 cases and 50 matched controls. Majority of subjects in both groups were males (n=31;62%),with male to female ratio of 1.6:1. Proportion of cases with iron deficiency anaemia were higher among cases(32%) as compared to controls(24%) but the difference between two groups was not significant statistically (p=0.373) despite having higher risk(OR=1.49;95% CI=0.62-3.59). Mean monocyte, oeosinophil and absolute oeosinophil count was found to be significantly higher in cases as compared to controls (p<0.05). Conclusion: The present study do not suggest a possible linkage between iron deficiency anemia and wheeze associated respiratory infection, however its role as causative factor needs to be explored through long-term prospective and intervention studies on a large population. J Nepal Paediatr Soc 2014;34(3):195-199 DOI: http://dx.doi.org/10.3126/jnps.v34i3.11378